Factors Affecting Small Medium Enterprises' (SMEs) decision to go International / Azurin Sani, Ahmad Shazeer Mohamed Thaheer and Zahariah Mohd Zain - Sani, Azurin; Mohamed Thaheer, Ahmad Shazeer; Mohd Zain, Zahariah (2018)
Small and Medium Enterprise (SMEs) have grown increasingly significant with the additional activity of exporting and has caught the attention of the experts. They have now grown to be the largest cluster of industry. SMEs also have the chance to be the dominant driver of export growth and suggest that SMEs actively participate in the export efforts, but the contribution diverge between countries. As they are participating in export between countries, indirectly they are veering towards internationalization. Internationalization provides a new business opportunity for innovation and new export markets, both upstream and downstream, with large firms between the SMEs themselves. SMEs are also viable for internationalization due to technological development, the deregulation of markets, the liberalization of world trade and the emergence of regional economic cooperation agreements. The study aims to identify the relationship between influential factors and SME's decision regarding internationalization. The influential factors were identified as external factors, internal factors and networking factors which considerably affect the decision of SME's regarding internationalization. Other than that, it also aims at assessing the most influential factor affecting internationalization of SMEs. The focus is on SMEs that are involved in international markets and registered as MATRADE members. The method used to conduct the survey is by distributing the questionnaire through email blasts to all registered SMEs. The total SMEs services companies under MATRADE databases are 300. Thus, the target respondents from the population which are 105 companies basically located in Klang Valley. Correlation analysis and regression were utilized to analyze the data and meet the research objectives. The expected outcome from this research project is to analyze the three influential factors; that is external, internal and networking that have the most influential effects on SMEs internationalization.